Practical management for the digital age : an introduction for engineers, scientists, and related disciplines - Baumers, Martin; Dominy, John (Professor of engineering) (CRC Press, 2022)
"This book is an accessible and comparatively short text that can comfortably be read cover-to-cover over the course of a semester. It has been written for readers with little or no prior knowledge of the concepts of management or experience in professional management activities. It forms an academically rigorous, accurate and consistent treatment of a subject that draws on a wide field rife with competing definitions, methodological variety, conceptual fuzziness, and inconsistent naming conventions. The book places a clear emphasis of the impact of information technology on the business world, drawing on recent literature and examples. Similarly, it highlights how environmental aspects are interwoven with management decision making, addressing the second theme of great urgency in management. Features: Forms a self-contained treatment of management for those without prior knowledge of management or commerce to provide a broad foundation, and explains how management principles and methods draw on rationality-based models of human behavior. Provides an introduction to ongoing financial and legal processes in businesses. Introduces readers to business management as an ongoing activity. Presents a view of sustainability in business that encompasses the environment, society, and the economy. Discusses methods for successful project management and the evaluation of projects and cash flows resulting from projects over time. Practical Management for the Digital Age: An Introduction for Engineers, Scientists, and Related Disciplines is aimed at a wide range of undergraduate and postgraduate students in a variety of fields, as well as practitioners. It is applicable to those in the fields of engineering, science, computer science, medicine, pharmacy, social sciences, and more. It helps readers to engage confidently in managerial situations later in their careers and during project work in the final parts of their degree courses. For instructors, who may not have a management background, this book offers content for a self-contained year-long course in management at the intermediate undergraduate level. In addition, it has been developed for undergraduate and postgraduate courses with accreditation requirements that include a taught element in management, such as the UK Engineering Council's Accreditation of Higher Education (AHEP) framework"--